DIPLOMASI BUDAYA INDONESIA UNTUK MEMPERKENALKAN PENCAK SILAT DI INGGRIS TAHUN 2018 - Ori Opilo (2021)
This thesis research examines Indonesia's cultural diplomacy to introduce Pencak Silat which is part of its soft power in British society in 2018. This thesis research also uses the concept of cultural diplomacy and national interests. Then use a qualitative method (case study) with the type of explorative research in the analysis process. This study found that cultural diplomacy carried out by Indonesia in the UK was pursued through two forms of activity, namely exhibition and special events for the first time in the history of British Pencak Silat. These activities can also assist Indonesia in its efforts to achieve national interests which are beneficial as seen from the achievements in the UK. Such as an increase in cultural promotion, an increase in the country's image, an increase in the number of British tourists coming to Indonesia, and an increase in the interest of British citizens in the traditional weapon of the Indonesian nation which is identical to PencakSilat, namely Karambit.